Magnetically controlled space charge capacitance at La1−xSrxMnO3/SrxLa1−xTiO3 interfaces. Issue 8 (10th March 2016) - Schmidt, Rainer; García‐Barriocanal, Javier; Varela, María; García‐Hernández, Mar; León, Carlos; Santamaría, Jacobo
Abstract : This work reports on magnetocapacitance (MC) effects in epitaxial heterostructures of nominally 15 unit cells (u.c.) LaMnO3 (LMO) and 2 u.c. SrTiO3 (STO) with an alternating layer‐repetition rate of 8: (LMO15 /STO2 )8 . Epitaxial multilayer growth at high temperatures (900 °C) activates a selective inter‐diffusion of La 3+ and Sr 2+ cations across the interfaces, which gives rise to Sr p‐doping of the LMO and La n‐doping of the STO layers. MC effects at the buried La1– x Sr x MnO3 /Sr x La1– x TiO3 (LSMO/SLTO) interfaces are probed by frequency, temperature and magnetic field dependent AC impedance spectroscopy. The technique is shown to be appropriate to account for the separate analysis of different resistance and capacitance contributions at the buried interfaces. As a result of the La/Sr inter‐diffusion process, Schottky barriers are formed at the LSMO/SLTO interfaces, which give rise to massive MC of up to ≈ −200% in the out‐of‐plane film direction. The capacitance of the manganite‐titanate LSMO/SLTO interfaces may be coupled indirectly to the resistance of the LSMO layers, because the Schottky space‐charge layers and their capacitance can be modulated by varying the concentration of highly mobile charge carriers in the LSMO with a magnetic field.